Assessment of production potential of water saving technologies on rice (Oryza sativa) in India - SAMAL, P; SINGH, O N; GHOSH, A (The Indian Journal of Agricultural Sciences, 2013)
The production of rice, the largest consumer of irrigation water, has been threatened due to demand from other sectors of the economy. Among the several options available for increasing water productivity, alternate wetting and drying (AWD) and use of aerobic rice cultures are two viable options and these two options were tried at on-station and on-farm level to assess and quantify the reduction in number of irrigations and their viability on farmers’ field. Participatory varietal selection method was used to select aerobic rice cultures and form the basis for further seed supply to farmers. Seeds of promising cultures were supplied to farmers and subsequently impact analysis was done. The impact analysis revealed that there are 2–3 irrigation saving due to adoption of AWD and new rice cultures and consequently, a cost of saving of ` 375/tonne of rice was obtained. The results of the simulation exercise revealed that irrigated rice area can be further expanded to another 3.0 million ha and rice production by another 7.2 million tonnes due to adoption of these technologies.